Pengaruh Kepemimpinan Dan Keinovatifan Terhadap Kinerja Perusahaan Pada Pt. Pelayaran Nasional Bahtera Bestari Shipping - Kwari Kristiani (Universitas Tarumanagara, 2019)
This study aims to determine the influence of Leadership and Innovativeness on Business Performance at PT. Bahtera Bestari Shipping. This research method using quantitative method. Data collection was done by distributing questionnaires to 100 employees of PT. Bahtera Bestari Shipping Shipping then data processed with SPSS program, after which the data is analyzed by using regression analysis. The results showed that there was an influence between Inovativeness and business performance of 69.2%. For the Leadership variable itself does not have an impact on business performance due to a decrease in the variables. The results of the analysis show that the influence between leadership and innovation variables on business performance where the company must develop innovation to develop the company's performance in order to maintain the company in the era of globalization competition in the world of shipping so that the company is able to diversify at international level.